Evidence of a Mixed Magnetic Phase in EuMgGe: A Semimetallic Zintl Compound with TiNiSi Structure Type 1. Issue 10 (5th June 2014) - Slabon, Adam; Cuervo‐Reyes, Eduardo; Niehaus, Oliver; Winter, Florian; Mensing, Christian; Pöttgen, Rainer; Nesper, Reinhard
Abstract The ternary Zintl phase EuMgGe was synthesized from the elements, and its structure solved by single‐crystal X‐ray diffraction. Chemical bonding is discussed, by means of electronic structure calculations at the DFT level and its physical properties characterized with respect to electronic conductivity, magnetic susceptibility, specific heat capacity, and magnetoresistivity. The compound may be interpreted according to the Zintl‐Klemm concept as (Eu2+)(Mg2+)(Ge4–) with isolated germanium anions. Resistivity measurements reveal a semimetallic character, which is consistent with the vanishing energy gap obtained from our calculations. The magnetic susceptibility and the specific heat indicate that two consecutive transitions take place, at 9 and 16 K, and they show evidence of magnetic frustration. A possible physical scenario for this magnetic behavior is discussed based on known models of partially frustrated magnets.